O conservadorismo na atualidade e seus rebatimentos na direção ético-política do Serviço Social - Silva, Adriana Brito da (2015)
This research aims to discuss conservatism today and its repercussions on the ethical-political direction of Social Work. Including the Marxist theoretical framework and the authors linked to it. It features brief historical background of conservative thought and their reproduction within the profession. It addresses some characteristics of the contemporary capitalist mode of production, ie. the flexible accumulation, the foundation support and justification of conservative ideology. It remarks some aspects of neoliberal politics and postmodern thought, as well as coexistence between conservatism and the ethical-political project nowadays. And finally, through field research, it demonstrates and discusses some current characteristics of conservative thought